2018
DOI: 10.1002/jwmg.21494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calf predation and nutrition on elk vital rates

Abstract: Demographic data indicated a population of elk (Cervus canadensis) in northern New Mexico had reduced juvenile recruitment, resulting in a concern over quality hunting opportunities. Following several years of low calf:female ratios of <25:100, we conducted a 4‐year study from 2009–2012 to identify reasons for poor recruitment and evaluated the role of predation and nutrition in limiting productivity. We captured and fixed ear‐tag radio transmitters to 245 elk calves (126 males, 119 females) to determine cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…But these differences should have plateaued after 2 years of age and any remaining differences were simply individual differences in size and condition. These results are consistent with the current understanding of differences in selection of elk by hunters versus large carnivores (Kunkel et al 1999, Wright et al 2006, Tatman et al 2018). Previous research has reported that wolves, bears, and mountain lions predated primarily calves or old individuals (Gunther and Renkin 1990, Zager and Beecham 2006, Rearden et al 2011, Horne et al 2019).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…But these differences should have plateaued after 2 years of age and any remaining differences were simply individual differences in size and condition. These results are consistent with the current understanding of differences in selection of elk by hunters versus large carnivores (Kunkel et al 1999, Wright et al 2006, Tatman et al 2018). Previous research has reported that wolves, bears, and mountain lions predated primarily calves or old individuals (Gunther and Renkin 1990, Zager and Beecham 2006, Rearden et al 2011, Horne et al 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Birth mass, calf condition, and maternal condition have been evaluated in the context of calf survival (Smith and Anderson 1998, Bender et al 2002, White et al 2010, Johnson et al 2019). Survival of calves has been examined in relation to forage biomass and predation by mountain lions or American black bears ( Ursus americanus ; White et al 2010, Griffin et al 2011, Eacker et al 2016, Tatman et al 2018). The majority of studies examining the effects of body condition and predation on survival have focused specifically on calves.…”
mentioning
confidence: 99%
“…Wildlife managers must obtain reliable estimates of vital rates to characterize and quantify populations to inform predictive models [1][2][3]. Furthermore, population parameters are critical in understanding the relationship of species to their environment [4,5] including the effects of habitat [6,7] and harvest management [8][9][10] on demography and population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Carnivore management programs designed to reduce carnivore populations and increase ungulate recruitment and population growth have been implemented in a variety of ecological systems from the boreal forest to sagebrush‐steppe ecosystems (Schwartz et al 2003, Hurley et al 2011). However, effects of these management programs on ungulate populations are debated and effects vary across ecological systems (Boertje et al 1996, Hayes et al 2003, White et al 2010, Hurley et al 2011, Keech et al 2011, Tatman et al 2018). Multiple, multi‐year studies of bear‐wolf‐moose ( Alces alces ) systems in Alaska, USA, found that predation was the dominant factor affecting moose survival and abundance, and, in many cases, experimental reductions of predators increased populations (see Boertje et al 2010 for review; but see also Hayes et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sources of uncertainty exist in the ecological processes and effects of management actions that occur between prescribing carnivore harvest regulations and achieving increases in ungulate recruitment. First, the carnivore harvest objective may not be achievable using hunter harvest (White et al 2010, Bischof et al 2012, Tatman et al 2018). Second, the achieved harvest may not result in a biologically significant change in carnivore abundance (Adams et al 2008, Robinson et al 2014).…”
Section: Introductionmentioning
confidence: 99%